Update on the Catastrophic Antiphospholipid Syndrome and the “CAPS Registry” - Cervera, Ricard; Espinosa, Gerard (Seminars in Thrombosis and Hemostasis, 2012)
Although less than 1% of patients with the antiphospholipid syndrome (APS) develop the catastrophic variant known as catastrophic antiphospholipid syndrome (CAPS), its potentially lethal outcome emphasizes its importance in clinical medicine today. However, the rarity of this variant makes it extraordinarily difficult to study in any systematic way. To collate all the published case reports as well as the newly diagnosed cases from all over the world, an international registry of patients with CAPS (“CAPS Registry”) was created in 2000 by the European Forum on Antiphospholipid Antibodies (www.med.ub.es/MIMMUN/FORUM/CAPS.HTM). Currently, this database documents the entire clinical, laboratory, and therapeutic data of more than 350 fully registered patients.
Keywords: catastrophic antiphospholipid syndrome; Asherson syndrome; antiphospholipid antibodies; anticardiolipin antibodies; lupus anticoagulant; antiphospholipid syndrome